The Relevance of Ibn Taymiyah's Thought Towards Contemporary Islamic Education Innovation - Suriadi (Mazidah: Journal Of Educational Research, 2026)
Islamic education is a field of study that continues to evolve in line with social dynamics and the demands of the times. Ibn Taymiyyah's thought is one of the important contributions in responding to various problems of the ummah through an educational approach based on Islamic values. This research aims to examine Ibn Taymiyah's educational thought which includes aspects of educational philosophy, objectives, curriculum, methods, language of instruction, and ethics of teachers and students, as well as analyze its relevance to contemporary Islamic educational innovations. This study uses a library research method with a descriptive qualitative approach. Data were obtained from various sources of classical and contemporary literature related to Ibn Taymiyyah's thought and Islamic education. The data was then systematically analyzed using descriptive-analytical techniques to find the relationship between the educational concepts offered and today's educational needs. The results of the study show that Ibn Taymiyah's educational thought has significant relevance to the development of contemporary Islamic education, both in terms of philosophical foundations, educational materials, and learning methods. The concept of education developed is based on the Qur'an and As-Sunnah with the approach of al-hikmah (wisdom), al-mau'izhah (good advice), and al-jadal al-ahsan (constructive dialogue). This approach emphasizes a deep, rational, and applicative understanding. Therefore, Ibn TThought, Ibn Taymiyah, Contemporary Islamic Educationaymiyah's thought can be used as a basis for innovation in designing an Islamic education system that is adaptive, integrative, and relevant to the times.